Avian immunology - Kaspers, Bernd; Schat, K. A. (Karel Antoni), 1944-; Gobel, Thomas W.; Vervelde, Lonneke (Academic Press, 2022)
Avian Immunology, Third Edition contains a detailed description of the avian innate immune system, encompassing the mucosal, enteric, respiratory and reproductive systems. The diseases and disorders it covers, include immunodepressive diseases and immune evasion, autoimmune diseases, and tumors of the immune system. Practical aspects of vaccination are examined as well. Extensive appendices summarize resources for scientists including cell lines, inbred chicken lines, cytokines, chemokines, and monoclonal antibodies. With contributions from the foremost international experts in the field, Avian Immunology 3rd, provides the most up-to-date crucial information not only for poultry health professionals and avian biologists, but also for comparative and veterinary immunologists, graduate students and veterinary students with an interest in avian immunology. Avian Immunology, Third Edition, is a fascinating and growing field and surely provides new and exciting insights for mainstream immunology in the future.